1991
DOI: 10.1159/000168305
|View full text |Cite
|
Sign up to set email alerts
|

Increased Release of the N-Terminal and C-Terminal Portions of the Atrial Natriuretic Factor Prohormone during Immersion-Induced Central Hypervolemia in Cirrhotic Humans

Abstract: The role of peptides from the N-terminus and C-terminus of the 126 amino acid (a.a.) atrial natriuretic factors (ANF) prohormone in modulating renal sodium and water handling in cirrhotic patients has not been defined. Eight cirrhotic individuals were evaluated; their mean basal circulating concentration of the C-terminus (a.a. 99–126; i.e., ANF) was 25 ± 2 fmol/ml, not different from the 22 ± 1 fmol/ml value found in 54 normal volunteers. On the other hand, the basal circulating concentrations of the whole N-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 22 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…In a clinical study, Vesely et al . (1991) found a maximal increase in both the N‐terminus and C‐terminus of ANP prohormone in cirrhotic patients in response to central hypervolaemia induced by water immersion.…”
Section: Discussionmentioning
confidence: 99%
“…In a clinical study, Vesely et al . (1991) found a maximal increase in both the N‐terminus and C‐terminus of ANP prohormone in cirrhotic patients in response to central hypervolaemia induced by water immersion.…”
Section: Discussionmentioning
confidence: 99%
“…Exclusion criteria included anyone with a creatinine level above 1.5 mg/dl, because these cardiac hormones increase in the circulation of persons with renal failure (18,19). Also excluded was anyone with cirrhosis and ascites, because these peptide hormones also increase in their circulation in this disease state (20,21). Patients' prescribed medications were not taken the day of the study.…”
Section: Methodsmentioning
confidence: 99%
“…Head-out water immersion manoeuvre in humans, which it is able to induce central hypervolemia, has shown that there is a normal release of ANP in this population [78]. Head-out water immersion manoeuvre in humans, which it is able to induce central hypervolemia, has shown that there is a normal release of ANP in this population [78].…”
Section: Cirrhosis With Ascitesmentioning
confidence: 99%